2010
DOI: 10.1124/mol.110.067652
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer-Specific Cytochrome P450 2W1: Intracellular Localization, Glycosylation, and Catalytic Activity

Abstract: Cytochrome P450 2W1 (CYP2W1) is expressed at high levels in colorectal cancer cells. Moreover, we have shown previously that a higher tumor expression is associated with less survival. In this study, we characterize post-translational modification, inverted endoplasmic reticulum (ER) topology, and catalytic activity of CYP2W1. The analysis of colorectal normal and cancer tissues and CYP2W1 overexpressing human embryonic kidney (HEK) 293 cells showed that a fraction of CYP2W1 is modified by N-glycosylation. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 31 publications
(53 reference statements)
1
45
1
Order By: Relevance
“…However, a cytochrome p450 was recently identified that faces the ER lumen and maintains enzymatic activity, suggesting that electron transfer from CPR can take place to either side of the ER membrane. 17 In addition to CPR, also biliverdin reductase (BVR), the enzyme that catalyzes the formation of biliruy. gottlieb et al…”
Section: Resultsmentioning
confidence: 99%
“…However, a cytochrome p450 was recently identified that faces the ER lumen and maintains enzymatic activity, suggesting that electron transfer from CPR can take place to either side of the ER membrane. 17 In addition to CPR, also biliverdin reductase (BVR), the enzyme that catalyzes the formation of biliruy. gottlieb et al…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies indicate that increased levels of CYP2W1 expression positively correlate with the degree of tumor malignancy, as well as with decreased 10-year survival in patients with colon cancer (12,13). So far, several groups have reported on the metabolism of a few candidate substrates (i.e., benzopyrene, sterigmatocystin, aflatoxin B1, lysophospholipids, and fluorobenzothiazoles) for CYP2W1 expressed in E. coli or mammalian cells (14)(15)(16)(17)(18)(19). However, the potential of CYP2W1 as a specific target in cancer chemotherapy remains hitherto unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for inoperable CRC, discovery of novel chemotherapeutic agents is imperative. It has recently been reported that novel AhR-inducible cytochrome P450 2W1 (CYP2W1) is overexpressed in human colon cancer tissue (11,12). CYP2W1 expression is tumor-specific and regulated by DNA methylation status, that is, hypomethylation in the body of CYP2W1 results in enhanced protein expression.…”
Section: Introductionmentioning
confidence: 99%